2012
DOI: 10.1111/j.1552-6569.2012.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

“Snake Fang” Sign without Carotid Stenosis on Duplex Ultrasonography Indicates High Risk of Artery‐to‐Artery Embolic Stroke

Abstract: In these two cases, duplex ultrasonography revealed free-floating thrombi developed at the distal region of small plaques. Aggressive treatment should be considered in a patient with thromboembolic stroke who has the small plaque presenting "snake fang" sign even if there is no stenosis or plaque vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Vassileva et al reported a few cases of free-floating thrombus of the nonstenotic carotid artery detected by colour duplex sonography in ischemic stroke patients [ 8 ]. Tatheishi et al described the “snake fang sign”, characterized by a protruding carotid plaque which was associated with free floating thrombus and ischemic stroke [ 14 ]. Our findings emphasize the advantages of a detailed sonographic examination of the peripheral arteries in cases of arterial embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Vassileva et al reported a few cases of free-floating thrombus of the nonstenotic carotid artery detected by colour duplex sonography in ischemic stroke patients [ 8 ]. Tatheishi et al described the “snake fang sign”, characterized by a protruding carotid plaque which was associated with free floating thrombus and ischemic stroke [ 14 ]. Our findings emphasize the advantages of a detailed sonographic examination of the peripheral arteries in cases of arterial embolism.…”
Section: Discussionmentioning
confidence: 99%